San Joaquin College of Law Moot Court Finals - Watkins, Howard::::::::: (1987)
Donna Tarte, C.D. Harbottle, Deloise Tritt and Todd Barsotti; Judges James Thaxter, Hollis Best and Gary Austin Deloise Tritt standing making her argument